STUDI TENTANG BENTUK, FUNGSI ORNAMEN DAN PENATAAN RUANG INTERIOR RUMAH GADANG KAJANG PADATI KOTA PADANG - Ir. Drs. Heldi, M.Si., Ph.D., Fernando Rullis, Drs. Efrizal, M.Pd., (Serupa The Journal of Art Education, 2018)
The purpose of this research is :1.Identifying the form of interior ornamentdesign of Rumah Gadang Kajang Padati in Padang City. 2. Identify the functionof interior ornament design of Rumah Gadang Kajang Padati in Padang City. 3.Explainng the Spatial Arrangement interior of Rumah Gadang Kajang Padati inPadang City.The research is located at Kalumbuak and Lubuk Lintah subdistrict Kuranjiin Padang City. It use quantitative method with descriptive approach.It carried out by field observations, interviews and collection of documentation. For analysis and data collection, by reducing data, presenting data and take aconclusion. To test the validity of data, done by data triagualiton.The results of research founded in the form of ornamental functions,there isthe name of the ornament that comes from the natural form of flora, fauna andgeometric,which are almost identical in each aspect and have the same function.There are ten ornaments have 2 kinds of areas, namely Aceh and Minangkabau.All the names and forms of these ornaments made in the form of large and small aspects, placed vertically, horizontally and regionally on Rumah Gadang.on the Spatial Arrangement interior is divided into top, front and side view.Keywords: Form, Function, Spatial